2015
DOI: 10.1016/j.jval.2015.09.709
|View full text |Cite
|
Sign up to set email alerts
|

Pen Devices for Insulin Administration Compared to Needle And Vial: Systematic Review of Literature and Meta-Analysis

Abstract: A363 life. When possible, meta-analysis was performed, evaluating the presence of heterogeneity and risk of publication bias. Otherwise, descriptive analysis of the available data was done. Results: Of the 10.348 original references scanned, 17 studies were finally selected, 7 experimental and 10 analytical. The population included was mainly adults, with type 2 diabetes. Important risk of bias was found in all of the articles, particularly the experimental ones. Meta-analysis was performed for glycemic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Insulin pens were also unavailable for most PCPs in this survey. Insulin pens have been associated with improved adherence and better self-management while remaining cost-effective [36][37][38]. Consideration should be given to expanding the existing Trinidadian public formulary to include rapid acting insulin and insulin pen devices for the benefits presented.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin pens were also unavailable for most PCPs in this survey. Insulin pens have been associated with improved adherence and better self-management while remaining cost-effective [36][37][38]. Consideration should be given to expanding the existing Trinidadian public formulary to include rapid acting insulin and insulin pen devices for the benefits presented.…”
Section: Discussionmentioning
confidence: 99%
“…It also showed a trend in favor of pen devices in the percentage of people who reached HbA1c <7% without significant heterogeneity. 32 The 17 studies that contributed to this meta-analysis together showed a clear long-term trend of fewer hypoglycemic events with pen device use, as compared with syringes. Although the link between dose accuracy of insulin pen devices and clinical outcomes is not strongly established in clinical studies, the higher accuracy of the dose delivered by pen devices may enable better glycemic control and a lower rate of hypoglycemia.…”
Section: Hba1c and Hypoglycemiamentioning
confidence: 92%
“…Of note, all reviewed articles were assessed as having some risk of bias, largely due to the lack of masking and insufficient explanation of randomization methods. 21 Several new insulin ''smartpen'' systems integrate the standard insulin pen with additional features. The Eli Lilly Memoir insulin pen was one of the first to track administered doses and can store the last 16 doses administered.…”
Section: Insulin Delivery Devicesmentioning
confidence: 99%